DEVELOPMENT OF A WEB-BASED MATERIAL MANAGEMENT SYSTEM FOR A WOODWORKING WORKSHOP - Eka Sulistya Putra; Indah Wahyuni (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
This research and development (R&D) study aimed to create a website for managing materials in the Woodworking Workshop of the Civil Engineering and Planning Education program and to evaluate its feasibility in terms of content and media. The development process adhered to the waterfall model, progressing through the stages of analysis, design, coding, testing, and maintenance. The development yielded a web-based material management application. The initial analysis phase identified the core problem: the absence of a proper material information system, which hampered need analysis and identification. The application was developed using hardware (a laptop with 8GB RAM and an AMD processor) and software including Google Site, Appsgeyser, MySQL, PHPMyAdmin, and relevant frameworks. Following the design and coding phases, the application underwent rigorous testing. The feasibility testing produced excellent results. Validation by a content expert resulted in a score of 97.22% (average 3.90), deemed "Feasible." A media expert validation yielded a score of 96.67% (average 3.87), also "Feasible." User assessment showed a score of 92.78% (average 3.73), categorized as "Feasible." Additionally, co-existence and device compatibility tests both achieved a 100% feasibility rate. Performance efficiency testing recorded an average load time of 0 seconds. In conclusion, the developed web-based material management application is highly feasible and met the "Very Satisfied" criterion based on all validation and testing results.